The use of stone at Ohalo II, a 23,000 year old site in the Jordan Valley, Israel - Spivak, Polina; Nadel, Dani (Journal of Lithic Studies, 2016)
A wide range of stones were found at the 22,000-24,000 year old lakeshore camp of Ohalo II, the Sea of Galilee, Israel. The well-preserved camp includes the floors of six brush huts, several open-air hearths, a grave, a midden, and small installations. Stones were found in all excavated loci. These include a small assemblage of basalt and limestone tools, among which bowls, grinding implements and weights are the most common. Use-wear analysis supports the identification of the grinding tools, suggesting that cereals were indeed processed with them, but not in an intensive manner. The presence of thousands of cereal grains as well as several sickle blades accord well these finds. Bowls were all shallow and only their fragments were found. Weights were likely used as fishing net sinkers. Limestone and basalt flakes indicate local knapping. Basalt and limestone fragments, shattered from heat, were abundant in all the excavated loci. Their original use is yet to be verified, but their shattering from heat was affirmed by a series of experiments. Stones were also used as wall supports. The range of types, contexts and activities reflected by stone tools and natural stones is unprecedented in other contemporaneous sites in the southern Levant.